ANALISA SEMIOTIKA TERHADAP PEMBENTUKAN CITRA DIRI JOKO WIDODO MELALUI MEDIA SOSIAL YOUTUBE - Jeanie Annisa; Ricky Widyananda Putra (Avant Garde, 2019)
Youtube is a communication tool that provides transmission of the value and flow of information in the form of video content that contains of semiotics. President Joko Widodo used it as a political communication to convey various information on state and daily activities to give some effect to build the formation of self-image. This study uses Sanders Pierce's semiotic theory and social media theory by Kaplan and Heinlein. This research methodology was using descriptive qualitative with secondary data collection. The results of this study indicate that youtube official account of President Joko Widodo's has formed a self-image construction through Sanders Pierce semiotic analysis "triangle meaning" such as objects, signs, and interpretants that can be found in visual forms such as images, colors and graphics and narrative text. This paper analysis 3 of 315 official Joko Widodo's vlog content, namely (1) #JKWVLOG Sneakers Story; (2) #JKWVLOG Young Leaders; (3) #JKWVLOG Invite Jan Ethes Sports.